Dissenting Opinion in the Indonesian Judicial System: An Epistemological Study - Ahmad Muzayyin Destuladoe; Zudan Arief Fakrullo (PT FORMOSA CENDEKIA GLOBAL, 2026)
Dissenting opinion is an important arrangement in contemporary judicial systems, represent the independence of judges and free will behind legal decisions. Its existence is recognized normatively in Article 14 of Law Number 48 the Year 2009 on Judicial Power in Indonesia. Those rules are often applied inconsistently and in ways that create a gap between the law says and judges act, diluting courts’ transparency and accountability. This article studies dissenting opinion through an epistemological concept, considering how legal truth is constructed, put to the test and justified in judicial reasoning. Legal knowledge: viewed as an epistemic construction created out of a dialectical interplay between empirical facts rational discourse. Accordingly, judicial truth cannot be reduced to opinion, or even to majority opinion. Such an account elevates dissenting opinion to a strategic epistemic role within this framework: it is internal controls on the reasoning of majority opinion, mirrors competing concepts of legal interpretation, reinforces judicial accountability and further codifies evolving areas of doctrine. This research focuses on transactions related to Decision Number 68/Pid. Sus-TPK/2025/PN. Jkt. Pst. The Decision shows that dissent dislodges majority confusion, especially in terms of the difference between loss to the state and criminal liability, the former being a descriptive fact and only the latter being normative. Consequently, the practice of dissenting opinion is not only a normative obligation but also an epistemic necessity for contemporary judicial systems in order to improve the quality, reasoning and legitimacy of judicial decisions.